HUBUNGAN USIA, PENDIDIKAN DAN PARITAS DENGAN PENGGUNAAN AKDR DI PUSKESMAS DOLODUO KABUPATEN BOLAANG MONGONDOW - Wiwin Windasari Ibrahim; Yuliana Misar; Fatmah Zakaria (Akademika, 2019)
The family planning program (KB) in Indonesia has been recognized nationally and internationally as one of the programs that has significantly reduced fertility rates. The purpose of this study was to determine the relationship between age, education and parity with the use of IUD . This research was conducted at Puskesmas Doloduo Bolaang Mongondow District on August 8 until September 30th. This research is an analytic correlation research using crosssectional approach . The population in this study are all active acceptors of 850 people in the are a of Puskesmas Doloduo Bolaang Mongondow Utara . Sample in research that researched 85 respondent, with technique of accidental sampling sampling. Based on the Research Methods show that there is a relationship of age, education, and parity with the use of akdr in Puskesmas Doloduo Bolaang Mongondow District. Because p value 0 ,025 (